Value of SPET/CT image fusion in the assessment of neuroendocrine tumours with 111In-pentetreotide scintigraphy - Moreira, AP (2011)
OBJECTIVE: The purpose of this study was to evaluate the impact and clinical value of anatomical-functional image fusion in the study interpretation and clinical management of patients with neuroendocrine tumours (NET) using somatostatin receptor scintigraphy (SRS) and combined transmission and emission tomography -- single-photon emission tomography/CT (SPET/CT). MATERIAL AND METHODS: Twelve patients (8 female and 4 male; age range 32-74 y, mean 56 y) with proven or clinically suspected NET were studied with routine planar SRS and SPET/CT at 2 and 24 hours after injection of 111-222 MBq 111In-Pentetreotide. Seven patients came for staging/follow-up and 5 patients for primary tumour localization with staging. Analysis of fused images (SPET/CT) was done on a patient basis, with separated evaluation of SPET, low-dose CT images and fusion images. The gold standard for presence or absence of malignancy was pathology or clinical and imaging follow-up data. RESULTS: SRS was negative in 6 patients and positive in 6. SPET/CT provided no additional information in 6 patients, including all 6 negative studies. SPET/CT improved localization of SPET detected lesions in 6 positive studies. It defined the extent of the disease and showed bone involvement in 3 of the 6 positive studies. SPET/CT affected the diagnostic interpretation in 6 patients (50 %) and induced changes of management in 3 (25 %). CONCLUSION: The results of this study indicate that combined anatomical-functional imaging with SPET/CT significantly improves tumour localization and characterization, contributing to a better therapeutic management of patients with NET.